Effect of CRM systems on customer retention in financial institutions: quantitative analysis - COBOS GUTIERREZ, CARLOS EDUARDO (2024)
Objective: This study aims to quantitatively assess the impact of customer relationship management (CRM) systems on customer retention in financial institutions. It seeks to understand how variables such as customer satisfaction, service quality, and switching barriers are influenced by the implementation of CRM systems Materials and methods: A quantitative methodology was used, with a correlational-descriptive design. Data were collected through surveys administered to 480 clients of various financial institutions, measuring variables such as service quality, customer trust, and switching barriers using Likert scales. The data were analyzed using correlation and multiple regression techniques. Results: The findings revealed a significant positive correlation between CRM implementation and customer retention, with a correlation coefficient of r = 0.59 (p < 0.01). In addition, switching barriers (β = 0.57, p < 0.01) and customer satisfaction (β = 0.31, p < 0.05) were identified as key factors influencing customer retention in financial institutions. Conclusions: The implementation of CRM systems in financial institutions has a positive impact on customer retention, improving both service quality and customer satisfaction. These results suggest that financial institutions that adopt CRM achieve higher customer loyalty, enhancing their competitiveness in the market. Continued investment in CRM technologies is recommended to optimize customer relationships.